Hubungan Rawat Gabung Dengan Kelancaran Produksi Asi Pada Ibu Post Sectio Caesarea Di Rumah Sakit Ibu Dan Anak Dwi Sari Tahun 2024 - Sari, Isra Purnama; Sulastri, Mepi; sari, Liya Lugita (Jurnal Kesehatan Mitra Sekawan, 2024)
According to prevalence data in several countries of breastfeeding such as Southeast Asia, namely 23.1% Thailand 51.2% Myanmar, and East Timor 52.2% (WHO, 2021). In Indonesia, joint care is carried out in line with the increase in breastfeeding, because it stimulates mothers to breastfeed their babies often with the rooming in technique (Sari, 2021). There is the hormone oxytocin in breastfeeding mothers, this hormone affects the psychological state of the mother because she can hug her baby so that the mother becomes calm and happy. Breast milk will also increase quickly because of the hormone so that babies who get breast milk feel more satisfied. It is known that the Relationship between Joint Care and Smooth Breast Milk Production in Mothers with Caesarean Section Partus at the Dwi Sari Mother and Child Hospital in 2024. Design of this research is descriptive correlation using a cross sectional study approach with the aim of determining the effect of joint care on the smoothness of breast milk production in post-CS mothers observed in the same time period, the number of samples in this study was rounded to 95. The sampling technique in this research was accidental sampling. Univariate Results Almost all respondents 73 (76.8%) were treated together, Most respondents 70 (73.7%) had smooth breast milk at the Dwi Sari Mother and Child Hospital in 2024. Bivariate results there is a correlation between joint care and smooth breast milk production in post-cesarean mothers at the Dwi Sari Mother and Child Hospital in 2024 with a P-value of 0.000. It is hoped that this research will equip students in learning about health science insights, as well as provide promotive and preventive efforts for managing joint care with smooth breast milk production.